DISTORSI TERHADAP ISLAM: - Jasafat Jasafat (Jurnal Ilmiah Peuradeun, 2014)
The fact that often happens is a conflict in the respective civilizations, both Western and Islamic seen from the Western media. However, the fact is the internal conflict of civilizations is not considered that the conflict is cultural destiny. Because this assumption is identical to what existed in the last century, when the race war through information technology is believed to be a worldwide phenomenon in the future. Information technology has a major role in shaping public opinion globally. The development of information technology makes the process easy to implement International communication. The communication process involves not only individuals, but also of mass communication with the wider community. Use of globalized mass media has an impact on community identity. This paper tries to see the image presented by the Western media related image of Islam. This analysis was carried out to examine the role that can be carried by the mass media in the process of improving and shaping the image of Islam.